Dinamika Revolusi Industri 4.0 Terhadap Knowledge Based Society Menuju Transformasi Indonesia Emas 2045 - Taufik Hidayat (Universitas Sebelas Maret, 2022)
Information and communication technology is closely related to the digitalization revolution in the industrial sector. The industrial revolution 4.0 as a step towards golden Indonesia of 2045, is expected to be able to bridge the ideals of the Indonesian nation with competence with a combination of skills and knowledge which is reflected through job behavior. Competence is not directly related to abilities. Intellectual (IQ) but more related to behavior (behavior). The purpose of this study was to determine the capacity and carrying capacity of the preparation the Golden Generation of 2045 based on empirical and descriptive data from various sources, using literature studies and ethnographic studies. Based on research, towards a knowledge based society in the transformation process can be started from the education sector, as a process of socialization and institutionalization (internalization). As a recommendation and follow up plan, the development of a community of practitioners is a strategy for developing a profession or community in a sustainable manner. The concept of community of practitioners has been widely applied by various professions, especially in education and academia. Thus, the potential of the Industrial Revolution 4.0 with the readiness of a knowledge based society has the ultimate goal of encouraging the birth of intellectual workers or knowledge workers who will determine the competitive advantage of the Indonesian nation, towards the transformation the Golden Indonesia of 2045.